The Legal Dynamics of Pacta Sunt Servanda in Community Agreements - Wijaya Natalia Panjaitan; Agustina Balik; Syadzwina Hindun Nabila (KRTHA BHAYANGKARA, 2024)
Pacta Sunt Seravanda is one of the principles applied in agreements made by the community. However, the fact is that many people do not know about this principle when making transactions in agreements. This study aims to examine the implementation of the Pacta Sunt Servanda Principle in the Agreement of the Sawai Village Community, North Seram District, Central Maluku Regency. The research method used is sociological legal research, which is a combination research method between doctrinal legal research methods and empirical legal research methods. The implementation of the principle of pacta sunt servanda in Sawai Village, North Seram District, Central Maluku Regency, both in land rights agreements and other agreements in the community must always be socialized as a form of binding agreements that are often made by the community in order to minimize disputes because one party feels disadvantaged and wants to renege on the agreement.